Innovating pedagogical practices: Broadening horizons through gamification and technological resources - Dourado, Solange Oliveira; Cruz, Emerson Júlio Sampaio da (Seven Editora, 2024)
This article discusses the importance of innovating pedagogical practices through gamification and technological resources. Gamification, which uses game elements to engage students in the learning process, can make classes more dynamic and motivating. Additionally, the use of technological resources like tablets, computers, and educational apps can facilitate access to content and enable personalized teaching. DOI:https://doi.org/10.56238/sevened2024.010-023